(untitled) (Bulletin KNOB, 2011)
The exhibition ’A monument full of stories’ in the Rotterdam church Laurenskerk was made by the design offi ce Kossmann.dejong exhibition architects, specialized in telling complex stories in theatrical, spatial designs. Form and contents of the exhibition were jointly developed, with the monumental church building itself and the history of Laurenskerk and the city of Rotterdam as starting points. The history of the building and its religious use were determinant factors for the choice of themes. Since Laurenskerk is not only used as a church but also as a music podium and generates income by means of commercial letting, the exhibition is set in the chapels of the church. Because of the diversity of subjects and the special character of the location, intensive consultations took place with third parties. The infl uence of the talks with the brainstorming group, stakeholders and users of the church, experts as regards contents, the buildings aesthetics Committee and the Committee on Monuments formed the design process to a great extent.